Investigation of Design Flow in Separate Sewer Systems of Kuantan, Pahang - Ngien, S. K.; Yap, H. T.; Tan, L. K.; Choo, C. M.
Flow design parameters such as per capita flow and design criterion are significant in the design of sewerage systems. Malaysian sewerage systems are designed according to the Malaysian Sewerage Industry Guidelines (MSIG). Wrong consideration of flow design parameters brings negative effects in terms of construction cost, human health and environmental issues. The purpose of this research is to analyze and compare the per capita flow as well as design criterion in the sewerage systems of Kuantan, Pahang to their counterpart in the MSIG. Flowrate data was collected from two residential areas, Taman Pandan Damai and Bandar Putra with duration of 49 days. Population equivalent (PE) survey was done at the selected site locations. The resultant PE is 2244 and 1694, respectively. ISCO 4250 Area Velocity Flowmeter was used to collect real time flowrate data with intervals of five minutes. Flowrate data is analyzed separately for weekday and weekend. The average per capita flow result obtained from the sites is 0.277m3/day/person which is 23% higher than the 0.225m3/day/person stated in MSIG. Meanwhile, the results of average design criterion was 3.02, 36% lower than the 4.7 mentioned in MSIG. This indicated that the design of the sewerage systems in Taman Pandan Damai and Bandar Putra were effective and is more than enough to cater to the PE surveyed. More data,especially from long-term period collection, is desirable to determine whether revision of the flow design parameters in MSIG is needed.